Offering help in Greek: Divergence from the native-speaker norm and developmental patterns in Greek FL learners' performance of offers. (Selected Papers on Theoretical and Applied Linguistics from ISTAL 2015. Edited by E. Agathopoulou, T. Danavassi & L. Efstathiadi., 2017)
This study investigates developmental patterns in the ability of Greek foreign language learners to make offers. Drawing data from role-plays and retrospective verbal reports it attempts to explore the initial offer strategies and the degree of insistence that learners of three different proficiency levels (lower intermediate, intermediate and advanced) employ when performing offers in different social situations. The results suggest that, although there is a great deal of grammatical and pragma-linguistic development in regard to both initial offer strategies and syntactic modification devices, this does not guarantee concomitant levels of socio-pragmatic development (cf. Bardovi-Harlig 1999).